Automation of the Formation of Organizational Technological Documentation - Korol, Elena; Barabanova, Tatyana; Kagan, Pavel (Applied Mechanics and Materials, 2015)
Today in Russia the urgent question of preparation of qualified specialists for the construction industry. Appearance of new types of work requires workers, foremen and superintendents know how most effectively to manage the construction process, and often it is impossible without a qualitatively prepared the technological card on a certain type of work. Routing is an integral part of the design and technological documentation. It is necessary to modernize the process of formation of technological cards and create a new one, following the trends of development of the construction industry. Use of modern information technologies for the formation of technological cards will eliminate a number of personnel issues facing the construction complex. Raise the level of preparation of design and technological documentation will be possible due to introduction of methods, models, algorithms for automation of documentation. The process of development of technological cards in construction is one of the most difficult and complex and, at the same time, the least automated. Therefore, development of new models and methods of automation, change the very process of creating this section of organizational and technological documentation, will allow to solve an actual problem of improvement of quality of formation of technological cards, reduce time and cost of construction. Methodological and theoretical basis of research includes: the theory and practice of CAD, system analysis and construction or for system architect, database design, theory of algorithms, thematic work of the authors, the normative documentation in the field.